An epidemiological study of poisoning cases in Babol (northern Iran) from 2015 to 2018 - Mohammad Barary; Marzieh Pirzadeh; Nastaran Rezaeian; Mahsa Dadashnia; Sara Mohammadi-Daniali; Fatemeh Pahlavani; Aliasghar Manouchehri; Sohrab Kazemi; Aliakbar Moghadamnia (Babol University of Medical Sciences, 2021)
Background: Poisoning is a major public health problem that constitutes a significant share of the global burden of disease. Previous studies conducted in this area indicated the importance of such epidemiological studies. The most critical impact of these studies is their effect on changing current regulations and, therefore, decreasing poisoning cases. We aimed to evaluate all poisoning cases with regard to the patients' demographics and the involved intoxicants. Methods: The present study was conducted to investigate all poisoning cases who were admitted during a three-year period. Causes of poisoning, hospitalization, management procedures and outcome of the cases were surveyed.  A total of 1448 patients referred to Shahid Beheshti Hospital (Babol, Iran) from 2015 to 2018. Results: More than half of the patients were females (51.7%), and the majority of poisoning cases were seen in patients aged between 15 to 25 years (34.2%). It was found that suicide made a large part of poisoning cases (65.6%), and females tend to attempt suicide more than males (64.3% vs. 35.7%, respectively). Also, regular drugs followed by club drugs were the most abundant toxic agents (52.1% and 23.3%, respectively). Aluminum phosphide (AlP) was the most lethal intoxicant in our study, accounting for 68.2% of all deaths. Conclusions: According to the results, it is concluded that the existing regulations for drug control and suicide prevention have not been efficient enough and further actions yet to be made to reduce the consequences of drug- and non-drug-related toxicities.